Development of a transition piece for a self‐erecting wind energy plant. Issue 2 (1st September 2021) - Korte, Sebastian; Pak, Daniel; Friehe, Mirko; Fontecha, Robert; Feldmann, Markus; Reese, Christian; Schmitz, Katharina
Abstract: For the construction of wind towers with large hub heights up to 200m, the FOSTA research project P1392 HYTOWER [1] investigated a concept for a self‐erecting wind energy plant with steel‐steel hybrid tower. A tubular steel tower is lifted inside a lattice tower using a strand lifting system. During this process the tubular steel tower is stabilized by hydraulic cylinders. A specially developed transition piece is used to accommodate the lifting system during the lifting process and to finally connect the two tower parts. In this paper, the erection process as well as the development of the transition piece is presented.